2006
DOI: 10.1007/s00134-006-0202-x
|View full text |Cite
|
Sign up to set email alerts
|

Virus infection in exacerbations of chronic obstructive pulmonary disease requiring ventilation

Abstract: Forty-six (43%) of the patients with COPD exacerbation requiring mechanical ventilation had a probable viral pathogen. Prodromal, clinical and outcome parameters did not distinguish virus from non-virus illness. PCR was the most sensitive whilst virus culture was the least of virus assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 38 publications
(54 reference statements)
10
78
1
5
Order By: Relevance
“…Greenberg documented that 27% of exacerbations in 62 prospectively followed patients with COPD were related to a viral etiology (45); picornaviruses, parainfluenza virus, and coronaviruses accounted for the majority of infections in this study. Other investigators have suggested that up to 60% of exacerbations have been associated with viral infections, including picornaviruses, respiratory syncytial virus (RSV), influenza, and human metapneumoviruses (46)(47)(48)(49)(50)(51). One prospective study of hospitalized patients with AE-COPDs found a viral pathogen in more than 48% of episodes (vs. 6.25% in the stable state), with a similar distribution of viral pathogens as previously noted (52).…”
Section: Virusessupporting
confidence: 55%
“…Greenberg documented that 27% of exacerbations in 62 prospectively followed patients with COPD were related to a viral etiology (45); picornaviruses, parainfluenza virus, and coronaviruses accounted for the majority of infections in this study. Other investigators have suggested that up to 60% of exacerbations have been associated with viral infections, including picornaviruses, respiratory syncytial virus (RSV), influenza, and human metapneumoviruses (46)(47)(48)(49)(50)(51). One prospective study of hospitalized patients with AE-COPDs found a viral pathogen in more than 48% of episodes (vs. 6.25% in the stable state), with a similar distribution of viral pathogens as previously noted (52).…”
Section: Virusessupporting
confidence: 55%
“…Previous studies have shown inconsistent patterns of viral infection in COPD exacerbations. In an Australian study of the patients with COPD exacerbations requiring ventilation, most exacerbation episodes occurred in winter and spring season suggesting high seasonal variation (Cameron et al 2006). Contrary to this, the positive rate of virus identification was highest in summer (July to September) in the results from Hong Kong (Ko et al 2007a).…”
Section: Discussionmentioning
confidence: 82%
“…This paradigm may apply particularly to the chronic airway disease found in chronic obstructive pulmonary disease (COPD) (1). In this case, bacterial infection of the lower airways is often associated with COPD exacerbation and progression (2), but more sensitive PCR-based technology detects respiratory viruses in the airway with high frequency as well (3)(4)(5)(6)(7). Moreover, viral challenge shows that viral infection alone is sufficient to induce COPD exacerbation and to lead to secondary bacterial infection with exacerbation (8,9).…”
Section: Introductionmentioning
confidence: 99%